Energy-Efficient Hybrid Power System Model Based on Solar and Wind Energy for Integrated Grids. (21st February 2022) - Jha, Nishant; Prashar, Deepak; Rashid, Mamoon; Khanam, Zeba; Nagpal, Amandeep; AlGhamdi, Ahmed Saeed; Alshamrani, Sultan S.
Abstract : Global energy needs have risen in recent years, and traditional energy sources such as fossil fuels are no longer viable. To meet the growing electricity demand, attention has moved to renewable energy sources such as solar and wind energy. Furthermore, the development of clean energy is vital for combating climate change. Various studies have shown the effectiveness of using hybrid systems (combination of solar photovoltaic and wind energy systems) for generating power. However, a significant amount of energy gets wasted. To prevent the wastage of energy, a dual-energy generation system for integrated grids has been suggested in this paper. The load data have been collected from various regions in Rajasthan, India. An optimal grid system configuration is designed using net present cost and cost per unit of energy. Other factors such as the tilt angle of PV array optimization, wind energy, and inverter optimization have also been used for increasing the reliability and stability of the system. Sensitivity analysis has been performed to analyze the effective variations of the capital costs on the developed system economy. The results obtained from the simulations show that the overall costs of generating electricity from diesel systems and nongrid-based systems have been reduced to 20% at 10% annual capacity shortage allowance. Upon cost analysis, we found that the total cost for installing the suggested system is 49, 500 USD, whereas for other systems, the costs came out as 66, 000 USD, 56, 500 USD, and 56, 300 USD, respectively.